The potential of oxygen and nitrogen species-regulating drug delivery systems in medicine - Sołtan, Michał; Bartusik-Aebisher, Dorota; Aebisher, David (Frontiers in Bioengineering and Biotechnology, 2022)
The focus of this review is to present most significant advances in biomaterials used for control of reactive oxygen/nitrogen species (ROS/RNS, RONS) in medicine. A summary of the main pathways of ROS production and the main pathways of RNS production are shown herein. Although the physiological and pathological roles of RONS have been known for at least 2decades, the potential of their control in management of disease went unappreciated. Recently, advances in the field of biochemical engineering and materials science have allowed for development of RONS-responsive biomaterials for biomedical applications, which aim to control and change levels of reactive species in tissue microenvironments. These materials utilize polymers, inorganic nanoparticles (NPs), or organic-inorganic hybrids. Thus, biomaterials like hydrogels have been developed to promote tissue regeneration by actively scavenging and reducing RONS levels. Their promising utility comes from thermo- and RONS-sensitivity, stability as a delivery-medium, ease for incorporation into other materials and facility for injection. Their particular attractiveness is attributed to drug release realized in targeted tissues and cells with elevated RONS levels, which leads to enhanced treatment outcomes and reduced adverse effects. The mechanism of their action depends on the functional groups employed and their response to oxidation, and may be based on solubility changes or cleavage of chemical bonds. When talking about antioxidants, one should also mention oxidative stress, which we call the imbalance between antioxidants and reactive oxygen species, which occurs due to a deficiency of endogenous antioxidants and a low supply of exogenous antioxidants. This study is a review of articles in English from the databases PubMed and Web of Science retrieved by applying the search terms “Oxygen Species, Nitrogen Species and biomaterials” from 1996 to 2021.